A real-time network approach for including obstacles and flight dynamics in UAV route planning. (July 2016) - Myers, David; Batta, Rajan; Karwan, Mark
The procedure presented within considers the problem of calculating flight time for unmanned aerial vehicles (UAVs) while incorporating a subset of important flight dynamics characteristics in an operational field that contains obstacles. These flight time calculations are parameter inputs in mission planning and dynamic reassignment problems. The addition of pseudonodes and the addition of penalties into the associated edge weights are the basis for how the network generation procedure includes flight dynamics. The procedure includes a method for handling pop-up targets or obstacles in a dynamic reassignment problem. To guarantee that the optimal path includes flight dynamics, a selective Dijkstra's algorithm computes the shortest path. A complex mission plan consisting of thirty targets and three obstacles is the largest test scenario of nine developed scenarios. Our network generation procedure, along with the shortest path calculations of all 992 node pairs of interest, solves in approximately one second. This procedure allows for the fast computation needed to generate parameters for use in a dynamic domain such as mission planning and dynamic reassignment algorithms.